2009
DOI: 10.1021/cm902861y
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Mesoporosity in LTA Zeolites by Organosilane Surfactant for Rapid Molecular Transport in Catalytic Application

Abstract: Supporting InformationFigure S1. NH 3 temperature-programmed desorption profiles for LTA zeolite samples: Na +ionic form of bulk zeolite (NaA-0), Na + -ionic form of mesoporous zeolite (NaA-2), Ca 2+ionic form of bulk zeolite (CaA-0), and Ca 2+ -ionic form of mesoporous zeolite (CaA-2). The CaA samples exhibit ammonia desorption at high temperature as compared to NaA, which indicates that the CaA samples have stronger acid sites. The mesoporous CaA-2 zeolite exhibits only a slight decrease of desorption peak i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
134
0
7

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(145 citation statements)
references
References 40 publications
(84 reference statements)
4
134
0
7
Order By: Relevance
“…Other mesoporous zeolites synthesized by the amphiphilic organosilane surfactants were LTA [122], and FAU [123]. On one hand, a detailed synthetic work was performed to control the mesoporosity in the hierarchical LTA zeolite [122].…”
Section: Direct Synthesis Of Hierarchical Zeolites By Dual Templatingmentioning
confidence: 99%
See 1 more Smart Citation
“…Other mesoporous zeolites synthesized by the amphiphilic organosilane surfactants were LTA [122], and FAU [123]. On one hand, a detailed synthetic work was performed to control the mesoporosity in the hierarchical LTA zeolite [122].…”
Section: Direct Synthesis Of Hierarchical Zeolites By Dual Templatingmentioning
confidence: 99%
“…On one hand, a detailed synthetic work was performed to control the mesoporosity in the hierarchical LTA zeolite [122]. The mesopore size was tailored from 6 to 10 nm controlling the surfactant amount.…”
Section: Direct Synthesis Of Hierarchical Zeolites By Dual Templatingmentioning
confidence: 99%
“…Therefore, a lot of strategies including top-down desilication by alkali treatment [9][10][11], and bottom-up directed by hard [12][13][14][15][16][17] and soft template [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] have been proposed to synthesize meso-micro or macro-meso-micro zeolites. However, desilication is not suitable for the zeolite at low Si/Al molar ratio such as FAU, LTA, etc.…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30][31][32][33][34] Among these methods, the organosilane template developed by Ryoo et al has shown high flexibility and versatility in the synthesis of mesoporous zeolite. [35][36][37][38] Herein, we design a new kind of organosilane (1,6-bis (diethyl(3-trimethoxysilylpropyl)ammonium) hexane) with a gemini-type structure for the synthesis of mesoporous zeolite. This template can be easily prepared from the ordinary precursor by a simple synthesis route, and it has been used as an effective mesoporogen for the synthesis of hierarchical porous ZSM-5 zeolite.…”
Section: Introductionmentioning
confidence: 99%